Solventless Microextration Techniques for Pharmaceutical Analysis: The Greener Solution - Mohamed, Heba M. (Frontiers in Chemistry, 2022)
Extensive efforts have been made in last decades to simplify the holistic sample preparation process. The idea of maximizing the extraction efficiency along with reduction of extraction time, minimization/elimination of hazardous solvents, miniaturization of the extraction device, eliminating sample pre-treatment and post-treatment steps; reducing the sample volume requirement is always the dream for an analyst as it ensure the method’s congruency with the Green Analytical Chemistry (GAC) principles and steps towards the sustainability. In this context, the micro extraction techniques such as s Solid Phase Micro Extraction (SPME), Stir bar Sorptive Extraction (SBSE), Micro Extraction by Packed Sorbent (MEPS), Fabric Phase Sorptive Extraction (FPSE), in-tube extraction-dynamic headspace (ITEX-DHS), PAL SPME Arrow have been a very active area of research and application. To help transitioning into broader applications, the new solventless microextraction techniques have to be commercialized, automated, validated and their operating principles to be anchored to theory. In this work, the benefits and drawbacks of the advanced microextraction techniques will be discussed and compared, together with their applicability to the analysis of pharmaceuticals in different matrices.